Enhanced Optical Properties of ZnO-TiO2 Films Through Co-Sensitization with Multiple Natural Dyes - Musyarofah, Musyarofah; Nuraini, Inas; Prayitno, Budi; Ernawati, Lusi; Ismail, Andi Idhil; Triwikantoro, Triwikantoro (Universitas Gadjah Mada, 2025)
The ZnO-TiO2 films were co-sensitized with single, double, and triple natural dyes, leading to distinct effects on the optical properties. ZnO (wurtzite) and TiO2 (anatase) were prepared from commercial powders and the XRD results revealed that the crystallite size is 158 and 443 nm, respectively. The UV absorbance of ZnO powder shows significant peaks at wavelengths of 255 and 345 nm, with a band gap energy of 3.07 eV. Meanwhile, TiO2 powder exhibits a maximum peak at 325 nm and possesses a band gap energy of 3.16 eV. The extraction of natural dyes (Moringa oleifera, Biancaea sappan, Matricaria chamomilla, Rosa, and Chrysanthemum) was carried out using a cost-effective and simple method involving immersion in ethanol for 2 × 24 h followed by filtration. FTIR test results show the presence of O–H, C–H, C=C, and C–O functional groups. The results of coating the ZnO-TiO2 film with natural dyes show that the UV spectrum peaks are higher than the visible light wavelength. Co-sensitization of double natural dyes demonstrated different effects on the ZnO-TiO2 film, i.e., achieved panchromatic absorption mainly in the UV wavelength spectrum.